Desenvolvimento e validação de questionário para avaliar conhecimentos e atitudes dos pacientes com artrite reumatoide sobre sua doença e tratamento - Rodrigues, Felipe Macário dos Santos (2022)
Rheumatoid Arthritis (RA) is a chronic autoimmune disease that causes inflammation and deformity in the joints. When the disease is not well controlled, it can cause functional disability, loss of productivity and worsening of quality of life. In light of this, there has been an increased focus on self-care strategies to help RA patients deal with the consequences of the disease. In this context, patient education is necessary, being an integral part of standard treatment, as reinforced by The European League Against Rheumatism (EULAR). This study aimed to develop and validate a questionnaire to assess knowledge and attitudes about the disease and treatment among patients with RA. This is a methodological study, which consists of investigating methods for obtaining, organizing and preparing data, referring to the construction and validation of a questionnaire. An integrative literature review was carried out to obtain the themes and sub-themes of the questionnaire. After that, the questionnaire was developed and the content was validated by a committee of experts in the area, measured through the content validity index (CVI), in which values ≥ 0.80 are satisfactory. Then, the pre-test of the questionnaire was carried out in patients with RA to prove the semantic validation. The structural validity of the questionnaire, tested by combinatorial factor analysis, was implemented using the Robust Diagonally Weighted Least Squares (RDWLS) estimation method. The adjustment indices used were: chi- square test (ꭓ2); chi-square/degree of freedom (ꭓ2/gl); Comparative Fit Index (CFI); Tucker-Lewis Index (Tucker-Lewis Index - TLI) and Root Mean Square Error of Approximation - RMSEA. Values of ꭓ2 should not be significant; the ratio ꭓ2/gl must be < 5; CFI and TLI values must be > 0.90 and RMSEA values must be < 0.08 with confidence interval (upper limit) < 0.10. The reliability of the score was measured through composite reliability, in which values above 0.7 are considered adequate. The themes identified in the literature review were: general knowledge of the disease, pharmacological and non-pharmacological treatment; beliefs and attitudes towards RA. The questionnaire developed from these themes presented satisfactory content validation with a total CVI of 0.95 and with a CVI of individual items ranging from 0.8 to 1. Of the 31 pre-test participants, 94% responded that the instrument was clear and understandable, proving its semantic validation. The proposed three-factor structure fitted the data well, with the value of ꭓ2 not being significant p = 0.354. The composite reliability of the three dimensions was adequate: 0.71; 0.75; 0.7. This study allowed the development of a new questionnaire to assess knowledge and attitudes towards disease and treatment of patients with RA, which had its content, semantics, structural validity and score reliability scientifically proven. Thus, the tests performed allow the applicability of the instrument as a tool that will help health professionals in conducting a structured and individualized health education.